Perilaku Seksual Menyimpang Sebagai Alasan Perceraian Pada Pengadilan Agama - Mahfuzah, Fadhilah; Putri, Helvia (LPPM Universitas Doktor Husni Ingratubun Papua, 2024)
Marriage is a relationship between a man and a woman. However, a decision was found in the Religious Court in the case of the wife's lawsuit after finding out that her husband had deviant sexual behavior. This normative legal research was carried out by analyzing the main legal material, namely the Religious Court Decision on divorce case Number 425/Pdt.G/2016/PA.Crp, as well as other secondary legal materials such as court decisions, legislation, legal theory. The results of this study show that the husband's sexual deviant behavior before marriage was not known to the wife until they entered into household life. After being married for a long time, the wives discovered that their husbands had deviant sexual behavior. Based on the judge's considerations in the three decisions, the wife as the plaintiff was the injured party on the grounds that her husband had deviant sexual behavior even though the regulations only confirmed this because of the frequent occurrence of disputes and disharmony in domestic life. Apart from that, the husband's deviant sexual behavior will not achieve the goals of marriage and in Islamic law sexual deviation is a prohibited act. The issue of deviant sexual behavior is feared to bring harm if the household is maintained.